Історіописання ленників і магнатів Речі Посполитої XV – першої половини XVII ст. як частина вітчизняної ранньомодерної історіографії - Вирський, Д. (Історіографічні дослідження в Україні, 2020)
Стаття є частинкою зібраних матеріалів з історії історіографії України доби Раннього Модерну. Історіописання є доброю проекцією потенціалу і амбіцій ранньомодерних політичних проектів. Але історики зазвичай зосереджені на “столичній” традиції. Утім, для представлення/конструювання української ранньомодерної історіографії часто-густо цікавіші пам’ятки з “околиць”. Нерідко вони слабко інтегровані до панівного історичного гранд-наративу держави, але мають далекосяжні інтелектуальні пропозиції. Ключовим для вітчизняної історіографічної традиції доби Раннього Модерну є простір річпосполитського історіописання рубежу XV/XVI – першої половини XVII ст. Його цікавою і слабко актуалізованою сучасними дослідниками ділянкою є історіографія ленників і магнатів Речі Посполитої. Спочатку коротко розглянуті пам’яток молдовського літописання (великолитовська історіописна традиція більш відома українському читачеві, тому її виведено за рамки цієї невеликої статті). До речі, історики Молдовського князівства-господарства писали церковно-слов’янською мовою. Далі так само коротко оглянуті пам’ятки магнатської історіографії України. Огляд доведений до часів Козацької революції середини XVII ст. і першої “дисертації” про козаків. The paper is a part of the collected materials on the history of historiography of Ukraine of the Early Modern period. Historiography is a good projection of the potential and ambitions of early modern political projects. But historians usually focus on the “capital” (metropolian) tradition. However, for the presentation / construction of Ukrainian early modern historiography, literary texts from the “neighborhood” are often more interesting. They are often poorly integrated into the dominant historical grand narrative of the state, but have the meaningful and farreaching intellectual proposals. The key to the domestic historiographical tradition of the Early Modern period is the space of the Polish-Lithuanian historiography of the turn of the XV / XVI – first half of the XVII century. His interesting and poorly updated area by modern researchers is the historiography of the vassal states and magnates of the Polish-Lithuanian Commonwealth. At first, the monuments of the Moldavian chronicle are briefly considered (the great Lithuanian historiographical tradition is better known to the Ukrainian readers, so it is taken out of the scope of this small paper). By the way, historians of the Moldavia XV–XVI centuries wrote in the Church Slavonic language. The following are a brief overview of the historical-literary texts of the magnate historiography of Ukraine. The review is brought to the times of the Cossack revolution of the middle of the XVII century and the first “dissertation” on the Cossacks (1653).